Influence of a Culture of Honesty and Exemplary Teachers on Student Character at Watuwali State Elementary School - Kusumo, Triswohadi; Lukman, Lukman; Haliadi, Haliadi (Journal of Education Method and Learning Strategy, 2024)
This research discusses the influence of a culture of honesty and teacher example on the character of students at Watuwali State Elementary School. The method in this research is quantitative with a descriptive approach. The population in this study was all Watuwali State Elementary School students for the 2023/2024 academic year, totaling 62 people. The instruments used in this research were an honest culture questionnaire, a teacher exemplary questionnaire, and a student character questionnaire. Based on the results of partial statistical analysis between honest culture and student character, the value obtained is tcount = 4.984 and ttable = 1.671 (tcount > ttable) and a significant value of 0.000 (0.000<0.05) so it can be partially concluded that there is an influence of honest culture on student character. The results of partial statistical analysis between teacher example and student character showed tcount = 5.066 and ttable = 1.671 (tcount > ttable) and a significant value of 0.000 (0.000<0.05) so it can be concluded that partially there is an influence of teacher example on student character. The results of the regression analysis show that the value of Fcount = 12.633 Ftable = 3.15 (Fcount > Ftable) and a significant value of 0.000 (0.000<0.05), so it can be concluded that there is a significant influence between the culture of honesty and teacher example on the character of students in state elementary schools. Watuwali academic year 2023/2024.